Estudio de dos alternativas de tecnologías no convencionales para el tratamiento de aguas residuales vertidas en el sector noroeste del humedal Guaymaral en la ciudad de Bogotá. (2018)
Wetlands can be considered as part of the main ecological structure of Bogota city, that is the reason this document presents two alternatives from non-conventional technologies for the treatment of wastewater (application to the soil and peat filters), reaching the Northwestern sector of Guaymaral wetland in order to seek the preservation and conservation of the natural area of the hydraulic rounds of wetland, where are today multiple human activities that have generated a remarkable deterioration in the wetland ecosystem, polluting surface water sources that are effluents from this mainly. Within the proposals will be evaluated mainly the removal yields of each one in order to determine which is the optimum for the treatment.